2020
DOI: 10.3340/jkns.2019.0154
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Safety and Effectiveness of Stent-Assisted Coil Embolization with Neuroform Atlas Stent in Intracranial Aneurysm

Abstract: Stent-assisted coil embolization (SAC) is commonly used for treating wide-neck intracranial aneurysms. In this study, we aimed to assess the clinical safety and efficacy of the NeuroForm Atlas Stent during SAC of intracranial aneurysms. Methods : We retrospectively analyzed data from patients with ruptured and unruptured cerebral aneurysms, who underwent SAC using the NeuroForm Atlas between February 2018 and July 2018. Favorable clinical outcomes and degree of aneurysm occlusion were defined as a modified Ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…Non-specific thromboembolic events were the most common thromboembolic complication while intra-procedure re-rupture was the most common hemorrhagic complication. 13 Retrospective 2010 42 0.7 Gao et al 14 Retrospective 2011 232 1.0 Kung et al 15 Retrospective 2011 131 0.8 Lodi et al 16 Retrospective 2011 22 0.7 Amenta et al 17 Retrospective 2012 65 0.8 Golshani et al 18 Retrospective 2012 36 0.8 Alurkar et al 18 Retrospective 2012 42 0.8 Santillan et al 19 Retrospective 2012 20 0.6 Li et al 20 Retrospective 2013 19 0.6 Giyek et al 21 Retrospective 2013 70 0.9 Chung et al 22 Retrospective 2014 72 0.8 Bechan et al 23 Prospective 2015 45 0.9 Li et al 24 Retrospective 2015 38 0.7 Yang et al 25 Retrospective 2015 211 0.8 Cai et al 26 Retrospective 2016 65 0.8 Zhao et al 27 Retrospective 2016 23 1.0 Muto et al 28 Retrospective 2016 40 0.7 Liu et al 29 Retrospective 2016 218 0.9 Liu et al 30 Retrospective 2017 113 0.9 Ho et al 31 Retrospective 2018 29 0.8 Zuo et al 32 Retrospective 2018 133 1.0 Roh et al 33 Retrospective 2019 38 0.8 Kim et al 34 Retrospective 2019 11 0.7 *Each article was assigned a quality score to stratify them based on risk of heterogeneity, 0 being high risk and 1 being low risk. Other hemorrhagic complications: 14 (9.5%) Infarction: 7 (4.6%)…”
Section: Resultsmentioning
confidence: 99%
“…Non-specific thromboembolic events were the most common thromboembolic complication while intra-procedure re-rupture was the most common hemorrhagic complication. 13 Retrospective 2010 42 0.7 Gao et al 14 Retrospective 2011 232 1.0 Kung et al 15 Retrospective 2011 131 0.8 Lodi et al 16 Retrospective 2011 22 0.7 Amenta et al 17 Retrospective 2012 65 0.8 Golshani et al 18 Retrospective 2012 36 0.8 Alurkar et al 18 Retrospective 2012 42 0.8 Santillan et al 19 Retrospective 2012 20 0.6 Li et al 20 Retrospective 2013 19 0.6 Giyek et al 21 Retrospective 2013 70 0.9 Chung et al 22 Retrospective 2014 72 0.8 Bechan et al 23 Prospective 2015 45 0.9 Li et al 24 Retrospective 2015 38 0.7 Yang et al 25 Retrospective 2015 211 0.8 Cai et al 26 Retrospective 2016 65 0.8 Zhao et al 27 Retrospective 2016 23 1.0 Muto et al 28 Retrospective 2016 40 0.7 Liu et al 29 Retrospective 2016 218 0.9 Liu et al 30 Retrospective 2017 113 0.9 Ho et al 31 Retrospective 2018 29 0.8 Zuo et al 32 Retrospective 2018 133 1.0 Roh et al 33 Retrospective 2019 38 0.8 Kim et al 34 Retrospective 2019 11 0.7 *Each article was assigned a quality score to stratify them based on risk of heterogeneity, 0 being high risk and 1 being low risk. Other hemorrhagic complications: 14 (9.5%) Infarction: 7 (4.6%)…”
Section: Resultsmentioning
confidence: 99%
“…There have been a few reports on SAC with Neuroform Atlas stents, of which most have reported that SAC using Neuroform Atlas stents is safe and effective in treating wide-necked aneurysms [ 1 , 6 , 7 , 13 , 14 ]. From their experience with 27 consecutive patients, the authors of one study concluded that Neuroform Atlas SAC is feasible for treating ruptured and unruptured wide-necked aneurysms that are not amenable to conventional coiling or clipping [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although SAC using the Neuroform Atlas stent has been reported to be safe and effective in treating wide-necked aneurysms [ 1 , 6 , 7 , 13 , 14 ], the technique has procedure-related complications that interventionists need to understand completely. However, none of those studies reported the incidence of and risk factors for procedure-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Initial experiences consisting of mostly retrospective and single centered investigations were published, but limitations were noted due to their study designs and a lack of patients or follow-up. [3][4][5][6][7][8][9][10][11][12][13] We therefore conducted a prospective and multicentric post-market study to determine the clinical and technical outcomes following treatment of intracranial aneurysms with the Neuroform Atlas stent.…”
Section: Introductionmentioning
confidence: 99%